A mixed method study on the impact of COVID-19 on mental healthcare in Ghana: rethinking mental health service delivery - Michael Zobi; Seth Kofi Abrokwa; Eugene Dordoye; Angel Phuti (BMC, 2024)
Abstract Background Since its emergence, Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) has caused severe health, social and economic challenges. Mental healthcare has been significantly affected globally, and even worse in developing countries. An emerging economy like Ghana in West Africa was not spared its disruptive effects. This study aimed to elucidate the impact of the coronavirus disease 2019, the COVID-19 pandemic (caused by SARS-CoV-2), on Ghana's mental healthcare system. Methods This is a mixed-method study using an emergent sequential exploratory design. A total of 15 front-line healthcare professionals were recruited from the three psychiatric hospitals, including the mental health department of a new teaching hospital in Ghana. Purposive sampling techniques and a semi-structured interview approach were used for recruitment and data collection. Quantitative data from hospital registries were collected and analysed to triangulate qualitative findings. Results Fifteen mental health workers were enrolled in the study. The mean age of participants was (34.47 ± 4.07) years, average work experience of (6.23 ± 3.64) years and the majority as males (60%). This study found an average decline of 23% in hospital attendance and a 35% decline in admissions in all four facilities compared to the previous year, 2019. The lived experiences shared by mental healthcare providers were grouped under 3 main themes: Adjustments to workplace regulations, accessibility to mental healthcare, and psychological wellbeing of mental healthcare workers. The fear of contracting SARS-CoV-2 among healthcare workers, medication shortages, and logistical challenges were also reported to affect Mental Health services during the pandemic. Conclusion This study highlights the challenges in mental healthcare during the COVID-19 pandemic in Ghana. The experiences encountered present an opportunity to gain insights into future pandemic preparedness and establish a framework for optimal mental healthcare delivery in Ghana.